Implementation of Triple Exponential Smoothing Method In The Number Of Divorce Rate In North Sumatra - Rio Derwanto (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
The number of divorce rates in North Sumatra from 2007 to 2020 has increased. The increase in the number of divorce rates in North Sumatra which has an impact on the mental condition of children is disturbed, so forecasting is carried out in order to reduce the number of future divorce rates in North Sumatra. The purpose of this study is to find out the results of the number of divorce rates in North Sumatra in 2021-2023 and to see which accuracy is more accurate between the Triple Exponential Smoothing Method. The comparison between Triple Exponential Smoothing Method which has more accurate forecasting, namely Triple Exponential Smoothing Method with parameter values  and MAPE values of 10,21%, obtains the equation for forecasting the number of divorce rates in North Sumatra is . The results of the study, the number of divorce rates in North Sumatra increased in 2021 with 12.765 cases and decreased in 2022 and 2023 with 11.708 cases and 10.271 cases respectively.